A review on the degradation of plastic waste under various environmental conditions / Nur Farah Izzati Hakmal - Hakmal, Nur Farah Izzati (2020)
Globally, due to the overwhelming plastic production, over a million tons of plastic waste were produced by every country in the world. Most of the plastic will end up at the landfill in which it constituted around 20-30% in municipal solid waste stream. However, about 40 percent million tons of plastic which could have been washed in the oceans, also ubiquitously found in land and waterways. The problem is the plastic wastes have created many environmental issues that threating human, flora and fauna even though it is claim as non-biodegradable. Studies found that plastic can be degraded until the micro size which pose more peril to the sustainable of ecosystem. Therefore, this study will review about the degradation of different type of plastic in different environmental conditions; water, soil, landfill and natural weathering. This includes the factors affecting plastic degradation by different degrading agents. The rate of degradation is also affected by both of the environmental conditions and characteristics of polymer. The changes in plastic properties such as tensile strength, carbonyl index, surface morphology and loss of weight corresponding to the exposure time are reviewed. Findings showed that the longer duration time of plastic exposure, the more the degradation effect on the plastics especially in its properties. Nevertheless, different types of plastic would have a different degradation effect as a result of different polymer and additives composition in the plastics. This review is important to support decision making on the recycling approach of plastic, fate of natural decomposition and renewable energy recovery from the degraded plastic. Other than that, improvement on the present status of landfilling practice and major waste polymer treatment technology can be attained from the review.